Consideration of mental health and well-being in high-level sport: When will a coach-centred approach be introduced? - Leprince, C.; Maurin, M.; Carling, C. (Sports Medicine, 2024)
Coverage of problems relating to mental health and well-being is gaining ground in the sports sector today, both in the media and in the scientific literature. Despite exposure to numerous stressors and suffering from poor mental health, coaches have in general been largely overlooked in the scientific literature. Previous studies have mainly focused upon athlete populations. The absence of research means that there are real shortcomings in both understanding the mechanisms involved in the deterioration of coaches` mental health and well-being and in the lack of specific support systems available. This paper first describes findings from the recent, albeit quite scarce, research investigating mental health and well-being in coaches. It then proposes a number of avenues for research and support protocols, both of which are currently ongoing at the French Football Federation Research Centre. The aim is to help support these key participants in the sports sector who arguably have not been given sufficient consideration until now.